Mobility Open Data: Use Case for Curitiba and New York - Nakonetchnei, Elis C.; Kozievitch, Nádia P.; Cappiello, Cinzia; Vitali, Monica; Akbar, Monika (Anais da Escola Regional de Banco de Dados (ERBD), 2017)
As cities are becoming green and smart, transportation systems are being revamped to adopt digital technologies. Open transportation data might include GIS maps for bus routes and bus stops. Such data provide a number of opportunities to analyze a segment of the current state of the transportation system of a city. In this paper, we address and discuss some of the urban mobility open data available and their characterization from the perspectives of two metropolitan cities: Curitiba (Brazil) and New York City (USA). Finally, we present challenges regarding their use.